Дослідження впливу компенсувальних установок на додаткові втрати активної потужності від несиметрії режиму - Терешкевич, Л.Б.; Червінська, Т.М.; Бандура, І.О. (Технічна електродинаміка, 2011)
Investigation of symmetric as well as asymmetriccapacitors battery influence on additional watt losses of mode asymmetry in grids of power supply organizations and power consumers are realized.